New Sunday Times, 12 August 2007 - Prabhakaran S. Nair (The New Straits Times Press (M) Bhd, 2007)
Tunku's achievement in steering the country to independence may be attributed to his ability to think differently. And it may be a useful exercise for us to take a peek into Tunku's thinking style on this 50th anniversary of our independence.